National estimates of intestinal ostomy creation and reversal for trauma. Issue 3 (9th March 2021) - Hashmi, Zain G.; Dalton, Michael K.; Sheikh, Saulat S.; McCarty, Justin C.; Salim, Ali; Haider, Adil H.
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: Intestinal ostomy creation after trauma is selectively indicated for destructive colon and rectal injuries. However, the nationwide rates of creation of ostomies for trauma and their reversal are not known. The objective of this study was to ascertain national estimates of trauma ostomy creation and reversal. METHODS: Weighted analysis of Healthcare Cost and Utilization Project Nationwide Readmissions Database 2014 to 2015 was performed. Adult trauma patients (≥16 years) with a hollow viscus injury were included. Patients with preexisting ostomies and permanent ostomies and those who died within 48 hours of admission were excluded. Rates of ostomy creation and same admission ostomy reversal were calculated. Rates of postdischarge ostomy reversal were calculated using the Kaplan-Meier estimator. Multivariable Cox proportional hazards model was used to determine factors associated with postdischarge trauma ostomy reversal. RESULTS: A total of 22, 542 patients sustained a hollow viscus injury resulting in the creation of 2, 145 ostomies (9.6%). The rate of same-admission ostomy reversal was 0.7% (n = 16). At 1, 3, 6, and 9 months, the cumulative stoma reversal rates were 0%, 7.6%, 31.0%, and 43.1%, respectively. The mean ± SD time from ostomy creation to reversal was 123 ± 6.7 days for those undergoing reversal. Injury Severity Score greater than 9 was significantly associated with ostomy nonreversal after discharge (hazard ratio, 0.41; 95% confidence interval, 0.26–0.66). Age, sex, insurance status, penetrating injury, Charlson Comorbidity Index, and hospital teaching status were not significantly associated with ostomy reversal. CONCLUSION: The nationwide rate of ostomy creation after trauma is nearly 10%. At 6 months postinjury, only one third of patients had undergone ostomy reversal. Future study is needed to understand patient and provider-level factors associated with trauma ostomy reversal. LEVEL OF EVIDENCE: Epidemiology, level III.